Bivariate genetic association of KIAA1797 with heart rate in American Indians: The Strong Heart Family Study - Melton, P.; Rutherford, S.; Voruganti, V.; Göring, H.; Laston, S.; Haack, K.; Comuzzie, A.; Dyer, T.; Johnson, M.; Kent, J.; Curran, J.; Moses, Eric; et al. (Oxford University Press, 2010)
Heart rate (HR) has been identified as a risk factor for cardiovascular disease (CVD), yet little is known regarding genetic factors influencing this phenotype. Previous research in American Indians (AIs) from the Strong Heart Family Study (SHFS) identified a significant quantitative trait locus (QTL) for HR on chromosome 9p21. Genetic association on HR was conducted in the SHFS. HR was measured from electrocardiogram (ECG) and echocardiograph (Echo) Doppler recordings. We examined 2248 single-nucleotide polymorphisms (SNPs) on chromosome 9p21 for association using a gene-centric statistical test. We replicated the aforementioned QTL [logarithm of odds (LOD) = 4.83; genome-wide P = 0.0003] on chromosome 9p21 in one SHFS population using joint linkage of ECG and Echo HR. After correcting for effective number of SNPs using a gene-centric test, six SNPs (rs7875153, rs7848524, rs4446809, rs10964759, rs1125488 and rs7853123) remained significant. We applied a novel bivariate association method, which was a joint test of association of a single locus to two traits using a standard additive genetic model. The SNP, rs7875153, provided the strongest evidence for association (P = 7.14 × 10-6). This SNP (rs7875153) is rare (minor allele frequency = 0.02) in AIs and is located within intron 9 of the gene KIAA1797. To support this association, we applied lymphocyte RNA expression data from the San Antonio Family Heart Study, a longitudinal study of CVD in Mexican Americans. Expression levels of KIAA1797 were significantly associated (P = 0.012) with HR. These findings in independent populations support that KIAA1797 genetic variation may be associated with HR but elucidation of a functional relationship requires additional study. © The Author 2010. Published by Oxford University Press. All rights reserved.